MANAJEMEN KEPEMIMPINAN DALAM PENGEMBANGKAN SKILL SANTRI (Studi Kasus Di Pondok Pesantren Mahasiswi Daruzzahra Arrifa’i Kota Malang) - Nury Firdausia (STAI Ma'had Aly Al-Hikam Malang, 2021)
Pesantren institution needs to change to positive things continuously because there is a hope for society from the output of pesantren. The development of the pesantren management is one of solution which used for increasing the quality of pesantren. The management will accompany and give an advice for the process of pesantren. Not unlike other educational institutions such as formal schools, pesantren education also requires management to develop or advance a pesantren. Management is an important thing in the management of Islamic boarding schools to continue and maintain the quality and progress of the pesantren. Pesantren whose management system is low or even bad, can result in reduced efficiency of a pesantren. Therefore, Islamic boarding schools need management, especially the leadership management of caregivers in developing the skills of their students